2012
DOI: 10.3116/16091833/13/2/74/2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transverse distribution profile of thulium on the performance of thulium-doped fibre amplifiers

Abstract: Abstract. We study numerical models for different transverse thulium distribution profiles (TTDPs) characterising the fibres used in thulium-doped fibre amplifiers (TDFAs). Our models consider the overlap factor and the absorption/emission dynamics. Basing on the radial TTDP function of the form, we show that the TDFA gain increases with increasing  parameter and decreases as the  parameter increases from 1 up to 3 µm, due to the overlap factor which affects the absorption and emission dynamics of the TDFA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The light in the EDF is assumed to propagate as a number of optical beams of frequency bandwidth Δ . The wave propagation of signal , pump ± and noise power ± can be expressed as [10] 2 1 ( ) ( ) ( ) ( ),…”
Section: Mathematical Modelling Of Edfamentioning
confidence: 99%
“…The light in the EDF is assumed to propagate as a number of optical beams of frequency bandwidth Δ . The wave propagation of signal , pump ± and noise power ± can be expressed as [10] 2 1 ( ) ( ) ( ) ( ),…”
Section: Mathematical Modelling Of Edfamentioning
confidence: 99%
“…n T (r) and n T are transverse distribution profile (TDP) of doped fiber amplifier (DFA) and total dopant concentration per unit per length defined by [12], [14]:…”
Section: Principle Of Macro-bend Pdcf Sensormentioning
confidence: 99%
“…It is found that in PDCF higher overlapping parameter turns out gain enhancement in active fiber [12]- [14]. The mode field distribution for PDCF in comparison with normal doped fiber falls outside the doping area at the bending situation and suffers more due to active bending loss [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this equation, E ðr ; '; !Þ refers to the guided mode's electric field, while N T is the total doping concentration of thulium ions per unit length, and n T ðr Þ represents the transverse distribution profile (TDP) of the TD-PCFA [21], [22]. The FV-FEM technique is utilized in order to calculate the electric field in the PCF fiber.…”
Section: Modeling Td-pcfamentioning
confidence: 99%